1999
DOI: 10.1021/ma982027x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Structure of Dendrimers in Solution by Small-Angle Neutron Scattering Including Contrast Variation

Abstract: The analysis of a dendrimer of fifth generation by small-angle neutron scattering (SANS) in solution is presented. The contrast of the solute toward the solvent dimethylacetamide (DMA) is changed systematically by measurements of the dendrimer in mixtures of deuterated with protonated DMA. Additional SANS measurements at highest contrast and varying dendrimer concentrations allowed to determine the structure factor of the dendrimers in solution. SANS intensities measured at different contrast are shown to yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
140
2
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 26 publications
13
140
2
4
Order By: Relevance
“…From a theoretical standpoint however, the continuous increase in dendrimer density with generation number leads to the prediction that a crossover generation exists where the available free volume inside the dendrimer vanishes. Considering the importance of the end groups for applications, this decrease in free volume with increasing G led numerous theoreticians and experimentalists [4,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] to question what became of the end groups in higher generation dendrimers as they might be trapped in the congested dendrimer interior. The first theory dealing with this issue was proposed by de Gennes and Hervet (DGH) [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a theoretical standpoint however, the continuous increase in dendrimer density with generation number leads to the prediction that a crossover generation exists where the available free volume inside the dendrimer vanishes. Considering the importance of the end groups for applications, this decrease in free volume with increasing G led numerous theoreticians and experimentalists [4,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] to question what became of the end groups in higher generation dendrimers as they might be trapped in the congested dendrimer interior. The first theory dealing with this issue was proposed by de Gennes and Hervet (DGH) [22].…”
Section: Introductionmentioning
confidence: 99%
“…A computational study carried out by Lescanec and Muthukumar [23] 12 years later contradicted the DGH prediction by finding that many terminal ends of a dendrimer do not remain at the dendrimer periphery but rather fold back into the dendrimer interior. Since then, numerous theoretical [12,13, and experimental [4,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] studies have been conducted which led to the current consensus [55] that the end groups of dendrimers made of a flexible backbone are distributed throughout the dendrimer interior in a core-dense manner. Only in a few rare studies were the terminal groups found to lay at the dendrimer periphery, when the ends were subject to some repulsive electrostatic forces [35,56,57] or attractive hydrogen-bond interactions [58] or the dendrimer was made of stiff repeating units [50].…”
Section: Introductionmentioning
confidence: 99%
“…Reports studying the molecular properties of dendrimers by different physical techniques are not numerous enough. In general, dendrimer molecules were studied by neutron scattering [9][10][11][12][13][14][15][16][17][18],…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest was the finding that chemical modification of the 'dip' of the Y-shaped pyridine 25 significantly enhanced the binding strength, resulting in a high binding constant ratio (K G4a / K G1a ) of up to 19 for 25. In sharp contrast, such an enhancement was not observed for an I-shaped derivative (24). The dendrimer shell did not act as a positive factor for other guests such as unsubstituted pyridine (1) and rigid I-shaped pyridines (4 and 10).…”
mentioning
confidence: 82%
“…However, the previous dendrimers were found to be suitable only for identification of simple and small guests [18][19][20][21][22] . Although dendrimers are potential containers for a larger guest or many guest molecules, they can become compact through back-folding of their terminal monomers towards the inside of the cavity, leading to loss of the cavity [23][24][25] . Meanwhile, dendritic structures with extra-rigid backbones do not participate to a significant extent in hostguest binding 26,27 .…”
mentioning
confidence: 99%